Factors influencing institutionalization of health technology assessment in Kenya - Mbau, R; Vassall, A; Gilson, L; Barasa, E (BioMed Central, 2023)
Background There is a global interest in institutionalizing health technology assessment (HTA) as an approach for explicit healthcare priority-setting. Institutionalization of HTA refers to the process of conducting and utilizing HTA as a normative practice for guiding resource allocation decisions within the health system. In this study, we aimed to examine the factors that were influencing institutionalization of HTA in Kenya.